Efek Penggunaan Beberapa Sinar LED pada Tanaman Buah Naga Merah (Hylocereus polyrhizus) - ADHIATMA DHIYAN SAPUTRA; I GUSTI ALIT GUNADI; I WAYAN WIRAATMAJA (Agrotrop : Journal on Agriculture Science, 2020)
Effects of Using Multiple LED Beams on Red Dragon Fruit (Hylocereus polyrhizus). Red dragon fruit plant (H. polyrhizus) is a tropical plant and is very adaptable to growing environments and weather changes such as sunlight, wind, and rainfall. Dragon fruit plants is a long day plants (plants that require long enough sun exposure), which means that to produce this plant requires at least 12 hours of radiation. Knowing this, there needs to be a solution so that production stability can be controlled, one of which is by modifying the environment. The purpose of this study was to determine the effect of several colors of LED light (Light Emitting Diode) at the initiation stage of dragon fruit flowers in an effort to increase production. This study used a randomized block design with four treatments and nine replications, while the treatment consisted of control plants, the administration of white LED lights, yellow LED lights and blue LED lights. Three variables were observed, namely the number of flower buds, the number of blooming flowers and the number of young fruits. The results showed that the use of yellow LED lights give the best light intensity when compared to other treatments so that the yellow LED light treatment gave the best results on each variable including 6.44 pieces for flower buds, 7.56 pieces for flowers blooms and 7.56 pieces for young fruit.